Saturated fatty acid biomarkers and risk of cardiometabolic diseases: A meta-analysis of prospective studies - Li, Zhaoqing; Lei, Haoyuan; Jiang, Hong; Fan, Yahui; Shi, Jia; Li, Chao; Chen, Fangyao; Mi, Baibing; Ma, Mao; Lin, Jing; Ma, Le (Frontiers in Nutrition, 2022)
Background and aims: Evidence regarding associations of circulating saturated fatty acids (SFAs) with chronic diseases is mixed. The objective of this study was to determine the associations between total or individual SFA biomarkers and the risk of cardiometabolic diseases. Methods: Four electronic databases were searched from inception to March 2022. Three investigators independently assessed for inclusion and extracted data. Random-effects or fixed-effects models was used to estimate the pooled relative risks (RRs) and corresponding 95% confidence intervals (CIs) for the association of total or individual SFA biomarkers, including even-chain SFAs (eg, 14:0, 16:0, 18:0), odd-chain SFAs (eg, 15:0, 17:0) and very-long-chain SFAs (VLCSFAs; eg, 20:0, 22:0, 24:0), with risk of incident type 2 diabetes (T2D), cardiovascular disease (CVD; coronary heart disease [CHD] inclusive of stroke), CHD and stroke. Results: 49 prospective studies reported in 45 articles were included. Higher concentration of circulating total SFAs was associated with an increasing risk of cardiometabolic diseases, the risk increased significantly by 50% for CVD (95%CI:1.31-1.71), 63% for CHD (95%CI:1.38-1.94), 38% for stroke (95%CI:1.05-1.82), respectively. Similarly, levels of even-chain SFAs were positively associated with higher risk of chronic diseases, with RRs ranging from 1.15 to 1.43. In contrast, the risk of cardiometabolic diseases was reduced with increasing odd-chain SFA levels, with RRs ranging from 0.62 to 0.91. A higher level of VLCSFAs corresponded to 19% reduction in CVD. Further dose-response analysis indicated that each 50% increment in percentage of total SFAs in circulating was associated with an 8% higher risk of T2D (RR: 1.08, 95%CI: 1.02-1.14) and trends toward higher risk of CVD (RR: 1.15, 95%CI: 0.98-1.34). Inverse linear relationships were observed between 17:0 biomarker and T2D or CVD risk. Conclusions: Our findings support the current recommendations of reducing intake of saturated fat as part of healthy dietary patterns. Further studies are needed to confirm our findings on these SFAs in relation to cardiometabolic outcomes and to elucidate underlying mechanisms.